Answer:
f(-4)=52
Explanation:
We are given the function:
![f(x)=2x^2-3x+8](https://img.qammunity.org/2021/formulas/mathematics/college/fpsd099h4uga0hu7m729fhe8mvu2hza52z.png)
We want to find f(-4), so we must substitute -4 in for x.
![f(-4)=2(-4)^2-3(-4)+8](https://img.qammunity.org/2021/formulas/mathematics/college/dgyfagwujngn9owkamwq60knnvfuklin1r.png)
Solve according to PEMDAS: Parentheses, Exponents, Multiplication, Division, Addition and Subtraction.
Evaluate the exponent first.
⇒ (-4)²= -4*-4 = 16
![f(-4)=2(16)-3(-4)+8](https://img.qammunity.org/2021/formulas/mathematics/college/958bbwmi9tzcebhm080dd5pzjsktlwtcig.png)
Multiply 2 and 16.
⇒ 2*16=32
![f(-4)=32-3(-4)+8](https://img.qammunity.org/2021/formulas/mathematics/college/fochspvrmjry4r56tgos5h2ga8b31r1a8a.png)
Multiply -3 and -4.
⇒-3*-4=12
![f(-4)=32+12+8](https://img.qammunity.org/2021/formulas/mathematics/college/ois15f68szly1krlslmbpr3uudwv20o3qi.png)
Add the three numbers together.
![f(-4)=44+8\\\\f(-4)=52](https://img.qammunity.org/2021/formulas/mathematics/college/s556rzjxmjd9w3q2icmtkej7uwssr4ofpk.png)
f(-4) for the function f(x)=2x²-3x+8 is equal to 52